MODEL LAYANAN INFORMASI LOKASI MASJID DI WILAYAH KOTA TANGERANG MENGGUNAKAN PERANGKAT BERGERAK (MOBILE DEVICE) - Angga Aditya Permana (Universitas Muhammadiyah Tangerang, 2016)
MuslimisthebiggestinhabitantinIndonesia,sothatthey needanextraordinary servicewhich canprovide informationabouttheirobligatory religiousactivity inthis caseissholat.Sholat is preferabledoneatmosqueespeciallyformale.Therefore, informationaboutthenearestmosque ismuchneeded,especiallyformobileusereven traveler. Thisinformationisimplicatedinmobile device,thereforeusercanaccess wheneverandwhereverasquickaspossible.Servicethatwillbe modeledinthis research exploiting Global Positioning System(GPS)on android mobile devices based on LocationBased Service (LBS).This servicemodel is developedfor providing information about location and historical background of mosquein Tangerang.Keywords: Android, Global Positioning System, Location Based Service, MobileDevice.